2020
DOI: 10.3390/en13030771
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Operation of Energy Storage Systems for Distributed Harmonic Compensation in Microgrids

Abstract: Energy storage systems (ESSs) bring various opportunities for a more reliable and flexible operation of microgrids (MGs). Among them, energy arbitrage and ancillary services are the most investigated application of ESSs. Furthermore, it has been shown that some other services could also be provided by ESSs such as power quality (PQ) improvements. This issue could be more challenging in MGs with widespread nonlinear loads injecting harmonic currents to the MG. In this paper, the feasibility of ESSs to act as co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…However, the control object with accurate mathematical model is required for the combination of PI and repetitive controller, and reasonable adjustment of parameters is needed to obtain optimal control. An optimization model to coordinate the control of harmonic compensation was proposed which enhanced the harmonic control capability of the energy storage system in [10]. It demonstrated that it is also important to utilize the model to investigate harmonic suppression.…”
Section: Lntroductionmentioning
confidence: 99%
“…However, the control object with accurate mathematical model is required for the combination of PI and repetitive controller, and reasonable adjustment of parameters is needed to obtain optimal control. An optimization model to coordinate the control of harmonic compensation was proposed which enhanced the harmonic control capability of the energy storage system in [10]. It demonstrated that it is also important to utilize the model to investigate harmonic suppression.…”
Section: Lntroductionmentioning
confidence: 99%